Pengembangan Komik Sejarah Berwaktu Pada Materi Peristiwa Rengasdengklok Sebagai Media Pembelajaran Sejarah Di SMA - Alexander Rendi Haditama Mumarta; Hera Hastuti (Jurnal Kronologi, 2023)
The background of this research focuses on the first aspects of learning history requiring media to visualize an event, secondly the lack of variety of media in the process of learning history, besides that the process of learning history is still focused on books so it has not been able to build elements of chronological thinking. This study aims to develop Indonesian history learning media on the Rengasdengklok incident material. Arranged in the order in which events occurred. This research is a Research and Development study with the ADDIE model which consists of five stages, namely: Analysis, Design, Development, Implementation and Evaluation. In this research process only reached the Development stage. The media validity test stage for Rental Comics was carried out by several experts in their fields, ranging from media experts to material experts. As for the practicality test stage, it was carried out by the history teacher and students of SMAN 1 Padang class IX IPS 2 using a questionnaire which was distributed directly to the class. The analysis of the results of the validity test of Indonesian historical material experts shows that it is in a very valid category with an average of 3.72. The results of the validity test by the media expert in Sewa Comic put it in the valid category with an average of 3.25. Furthermore, the analysis of Comic Rental media as a learning medium from history teachers obtained an average of 3.93 with a very decent category. The next stage is to practice the use of media in class IX IPS 2 by distributing questionnaires. The results of the practicality test of Sewa Comic media conducted by students obtained an average result of 3.60 which placed it in the very feasible category. Latar belakang penelitian ini memfokus kepada beebrapa aspek pertama pembelajaran sejarah membutuhkan media untuk memvisualisasikan sebuah peristiwa, kedua kurang bervariasinya media dalam proses pembelajaran sejarah, selain itu juga karena proses pembelajaran sejarah masih berfokus kepada buku sehingga belum mampu untuk membangun unsur berpikir kronologis. Penelitian ini bertujuan untuk mengembangkan media pembelajaran Sejarah Indonesia pada materi peristiwa Rengasdengklok. Yang disusun berdasarkan ururtan terjadi peristiwa. Penelitian ini merupakan penelitian Research and Development dengan model ADDIE yang terdiri lima tahap yaitu : Analysis, Design, Development, Implementation dan Evaluation. Pada proses penelitian ini hanya sampai pada tahap Development. Untuk tahap uji validitas media Komik Sewa dilakukan oleh beberapa ahli dibidangnya mulai dari ahli media, sampai ahli materi. Sedangkan untuk tahapan uji praktikalitas dilakukan oleh guru sejarah dan siswa SMAN 1 Padang kelas IX IPS 2 dengan menggunakan angket yang disebarkan langsung ke dalam kelas. Analsis hasil uji validitas ahli materi sejarah indonesia menunjukkan pada kategori sangat valid dengan rata rata 3,72 . Hasil uji validitas ahli media Komik Sewa menempatkan pada kategori valid dengan rata rata 3,25 . Selanjutnya analisis media Komik Sewa sebagai media pembelajaran dari guru sejarah diperoleh rata rata 3,93 dengan kategori sangat layak. Tahapan berikutnya ialah mempraktikan pemanfaatan media ke dalam kelas IX IPS 2 dengan cara menyebarkan angket. Hasil dari uji praktikalitas media Komik Sewa yang dilakukan oleh siswa memperoleh hasil rata-rata 3,60 yang menampatkan pada kategori sangat layak.